In Vitro Regeneration of Aromatic Rice (Oryza Sativa L. Var. Doairgura) (Bangladesh Journal of Botany, 2022)
Rice (Oryza sativa L.) is the world’s most important cereal crop. The Doairgura variety (O. sativa L.) is a low-yielding, high-quality aromatic rice-producing variety in Bangladesh. This study was undertaken to develop an in vitro regeneration protocol through in vitro callus induction. MS media supplemented with different concentrations of 2, 4- D (0.5, 1.0, 2.0 and 3.0 mg /l) were used for callus induction from the mature dehusked rice seeds. The best results for callus formation was obtained on MS media supplemented with 2.0 mg/l 2, 4-D. Shoot regeneration from in vitro cultured callus was tested with different combinations (BAP, NAA, Kn mg/l) of hormone containing MS media. The highest regeneration frequencies (100%) as well as the highest average shoot per culture (15.3) were recorded on the MS media supplemented with 2.0 mg/l BAP and 1.0 mg/l NAA. For root induction, hormone free MS media showed better results. After hardening, the plantlets were transferred to soil. This protocol is relatively simple and reproducible.Bangladesh J. Bot. 51(4): 677-682, 2022 (December)